Prevalence and pattern of cardiovascular magnetic resonance late gadolinium enhancement in highly trained endurance athletes - Domenech-Ximenos, B.; Sanz-de la Garza, M.; Prat-González, S.; Sepúlveda-Martinez, A.; Crispi, F.; Duran-Fernandez, K.; Perea, R. J.; Bijnens, B.; Sitges, M. (Journal of Magnetic Resonance Imaging, 2020)
Background: Intensive endurance exercise may induce a broad spectrum of right ventricular (RV) adaptation/remodelling patterns. Late gadolinium enhancement (LGE) has also been described in cardiovascular magnetic resonance (CMR) of some endurance athletes and its clinical meaning remains controversial. Our aim was to characterize the features of contrast CMR and the observed patterns of the LGE distribution in a cohort of highly trained endurance athletes. Methods: Ninety-three highly trained endurance athletes (> 12 h training/week at least during the last 5 years; 36 ± 6 years old; 53% male) and 72 age and gender-matched controls underwent a resting contrast CMR. In a subgroup of 28 athletes, T1 mapping was also performed. Results: High endurance training load was associated with larger bi-ventricular and bi-atrial sizes and a slight reduction of biventricular ejection fraction, as compared to controls in both genders (p < 0.05). Focal LGE was significantly more prevalent in athletes than in healthy subjects (37.6% vs 2.8%; p < 0.001), with a typical pattern in the RV insertion points. In T1 mapping, those athletes who had focal LGE had higher extracellular volume (ECV) at the remote myocardium than those without (27 ± 2.2% vs 25.2 ± 2.1%; p < 0.05).